Unified Theory of Acceptance and Use of Technology (UTAUT) Model on the Use of E-Commerce -Based Ac-counting Information Systems in MSMEs - Sellia Agustari; Fadli Fadli (International Journal of Economics and Management Research, 2026)
This study aims to examine the factors influencing the use of e-commerce–based accounting information systems (AIS) among Micro, Small, and Medium Enterprises (MSMEs) in Bengkulu City by applying the Unified Theory of Acceptance and Use of Technology (UTAUT) model. The variables analyzed include performance expectancy, effort expectancy, social influence, facilitating conditions, behavioral intention, and use behavior. This research employs a quantitative approach using primary data collected through an online questionnaire distributed to MSMEs that have implemented e-commerce–based AIS. A total of 120 respondents were selected using purposive sampling, and the data were analyzed using Partial Least Squares–Structural Equation Modeling (PLS-SEM) with SmartPLS software. The results indicate that performance expectancy, effort expectancy, and social influence have a positive and significant effect on behavioral intention. Furthermore, facilitating conditions and behavioral intention significantly influence the actual use behavior of e-commerce–based AIS. The model demonstrates good reliability, validity, and predictive relevance, confirming the suitability of the UTAUT model in explaining technology acceptance in the MSME context. These findings suggest that perceived benefits, ease of use, social support, and adequate infrastructure play crucial roles in encouraging MSMEs to adopt and continuously use e-commerce–based accounting information systems. This study contributes to the literature on accounting digitalization and provides practical insights for MSMEs and policymakers in promoting technology adoption to enhance financial management efficiency and business competitiveness.